On two Byzantine medical recipes in verse and the cultural climate of their composition. Fragments from Michael Psellus’ Medical Iambic Poem and Nikephoros Blemmydes’ canticle ‘On Urines’ - Diamandopoulos, Athanasios (DELTOS, 2025)
In the previous issue of Deltos,1 we published Part A of the article entitled Greek Medical Recipes in Verse: Their Position in the World. That instalment examined the origins of versified medical recipes and presented examples from the Classical, Hellenistic and Roman periods. It concluded with the De medicamentis liber, a poem attributed to Marcellus Empiricus and dated to the 4th or 5th century AD. In this Part B of the same article, we continue our exploration with a focus on similar recipes from the Middle and Late Byzantine periods. This section also includes examples from Medieval and Early Renaissance Latin and Islamic medical literature, thereby illustrating the intercultural context within which these Greek verses were situated. A general discussion and concluding remarks are provided at the end. 1. Diamandopoulos A. On some ancient Greek and Latin medical recipes in verse. Their position in the world. Part A. DELTOS [Internet]. 2024 Jul 1 [cited 2025 Jul 7];34(52):9–22. Available from: https://ejournals.epublishing.ekt.gr/index.php/deltos/article/view/38306/28551